The Organization of the Sinoatrial Node Microvasculature Varies Regionally to Match Local Myocyte Excitability. Issue 4 (12th June 2021) - Grainger, Nathan; Guarina, Laura; Cudmore, Robert H; Santana, L Fernando
Abstract: The cardiac cycle starts when an action potential is produced by pacemaking cells in the sinoatrial node. This cycle is repeated approximately 100 000 times in humans and 1 million times in mice per day, imposing a monumental metabolic demand on the heart, requiring efficient blood supply via the coronary vasculature to maintain cardiac function. Although the ventricular coronary circulation has been extensively studied, the relationship between vascularization and cellular pacemaking modalities in the sinoatrial node is poorly understood. Here, we tested the hypothesis that the organization of the sinoatrial node microvasculature varies regionally, reflecting local myocyte firing properties. We show that vessel densities are higher in the superior versus inferior sinoatrial node. Accordingly, sinoatrial node myocytes are closer to vessels in the superior versus inferior regions. Superior and inferior sinoatrial node myocytes produce stochastic subthreshold voltage fluctuations and action potentials. However, the intrinsic action potential firing rate of sinoatrial node myocytes is higher in the superior versus inferior node. Our data support a model in which the microvascular densities vary regionally within the sinoatrial node to match the electrical and Ca 2+ dynamics of nearby myocytes, effectively determining the dominant pacemaking site within the node. In this model, the high vascular density in the superior sinoatrial node places myocytes with metabolically demanding, high-frequency action potentials near vessels. The lower vascularization and electrical activity of inferior sinoatrial node myocytes could limit these cells to function to support sinoatrial node periodicity with sporadic voltage fluctuations via a stochastic resonance mechanism. Graphical Abstract: